An Exploratory Case Study on Performance Enhancement of ERP Projects - Parthasarathy, S.; Anbazhagan, N.; Ramachandran, Muthu (INFOCOMP Journal of Computer Science, 2007)
Business information system is an area of the greatest significance in any business enterprise today. Enterprise Resource Planning [ERP] projects are a growing segment of this vital area. These software systems are designed and installed by ERP vendors. Most current research on the subject concerns only managerial issues. This study is to probe the performance of ERP software in terms of the three crucial technical factors that determine the success or failure of a given ERP software. To probe these research issues, an exploratory case study was conducted with a survey and interview at a large organization with an ERP system. The statistical analysis of the collected data supports the three hypotheses of the study, leading to the conclusion that the crucial technical factors for ERP implementation are the same in literature and in the companies with successful ERP implementation. The future research study will involve other technical aspects of ERP implementation for enhancing its performance.